Anion detection by electro-insertion into N,N,N ',N '-tetrahexylphenylenediamine (THPD) microdroplets studied by voltammetry, EQCM, and SEM techniques - Marken, F; Compton, R; Goeting, C; Foord, J; Bull, S; Davies, S (1998)
The electrochemical oxidation and re-reduction of N′,N′,N,N-tetrahexylphenylene diamine (THPD) deposited in form of microdroplets on a basal plane pyrolytic graphite or gold electrode is shown to be a chemically reversible process in the presence of aqueous electrolyte media containing NO-3, SCN-, ClO-4, or PF-6. Sharp voltammetric responses with a mid point potential, Emid, characteristic of the type of anion and its concentration are observed. The oxidation product, an ionic liquid, undergoes rapid ion exchange when the anion of the aqueous electrolyte is exchanged with anions of lower Emid replacing anions of higher Emid. Although the effect of the supporting electrolyte cation in the case of the alkali metals K+, Na+, and Li+ is not significant, a considerable change in the voltammetric peak shape and Emid occurs in the presence of protons. This effect, attributed to the protonation of THPD, is also sensitive to the type of anion present with anions of lower Emid causing more facile protonation. After protonation of THPD, oxidation and re-reduction can be shown to be associated with H+ expulsion and uptake. Deposited onto the rough surface of a gold coated planoconvex quartz crystal oscillator the [THPD+ClO-4]oil deposit can be observed in form of micron-sized droplets in SEM images. A strong frequency response of the crystal oscillator in an electrochemical quartz crystal microbalance experiment associated with the oxidation and re-reduction of THPD can be detected but is not related to changes in mass. Rather, this frequency response may be attributed to changes in the viscosity and/or coverage of the oily deposit.